Adsorption Properties of Zeolite-Containing Microspheres and FCC Catalysts Based on Ukrainian Kaolin - L. Patrylak; R. Likhnyovskyi; V. Vypyraylenko; R. Leboda; J. Skubiszewska-Zięba; K. Patrylak (Adsorption Science & Technology)
A series of samples of zeolite-containing microspheres (ZCMS) and fluid catalytic cracking (FCC) catalysts based on Prosyana (Ukraine) kaolin were synthesized in situ. Their adsorption and chemisorption characteristics were recorded using a nitrogen low-temperature adsorption/desorption method and temperature programmed desorption (TPD) of ammonia, respectively. It was shown that changes in the synthesis conditions had a considerable impact on the micro- and meso-porosity of the samples. A low-temperature band dominated the ammonia TPD spectra of the ZCMS samples, reflecting the retention of ammonia by the sodium cations of the zeolite acting as weak Lewis acid sites. ZCMS was found to display an appreciable activity in cumene cracking at 723 K. It was shown that during the conversion of ZCMS to FCC catalysts through the decationization and ultra-stabilization of the zeolite phase, the latter is appreciably destroyed giving rise to a considerable increase in the mesoporosity of the samples without any change in the average diameters of such mesopores. It was concluded that the catalyst stability is characterized by pores of an intermediate (20–30 Å) diameter, thereby demonstrating the strength of the linkage between the zeolite and matrix phases. The zeolite phase content and adsorption characteristics of catalysts prepared on the basis of Prosyana kaolin meet the demands of modern FCC catalysts.